Natural State Modelling of Salak Geothermal Field - allen haryanto lukmana (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2020)
The Awibengkok geothermal field, also known as Salak, is a liquid-dominated field. The commercial Awibengkok reservoir is a moderate-to-high temperature (240–312 ◦C) geothermal resource with high fracture permeability, moderate porosity, and moderate-to-low matrix permeability, and can generate electricity up to 377 MW. This field fracture-controlled reservoir has benign chemistry and low-to-moderate non-condensable gas content. The geothermal reservoir is associated with youngvolcanism and intrusions in a highland area in the west of Salak Mountain and east of the Cianten caldera, a collapsed andesitic stratocone. In this paper, numerical method for calculation is used for modelling and reservoir simulation. A simulator is used to build the model. The model was built until it reached the natural state. The method used for model calibration is through pressure and temperature matching of two wells P-T logging data. One of the well is located on the western region of Salak geothermal field, while the other is located on the eastern region. Salak geothermal field model would reach natural state with simulation time up to millions of years. The model state the field is a liquid-dominated field and has steam caps in western and eastern area. The material on those two areas are different, thus the initial conditions are different. The temperature is higher in the western area. The gas saturation vary between 0.127 to 0.5 and there is a caprock with permeability 9mD.